Biblioteca, educação e literacia informacional em Portugal: resultados iniciais do projeto elit.pt - Silva, Armando Malheiro da (2016)
The present work contains part of the results of a research project entitled The information literacy in the European Higher Education: study of the situation of information skills in Portugal (eLi.pt) that was funded by the Foundation for Science and Technology. In it is studied the level of information literacy of Portuguese university students and secondary school. In this initial approach we present data from the questionnaire applied to a sample of 1624 students from educational institutions of Porto, Vila Real, Bragança, Coimbra, Covilhã, Castelo Branco and Lisboa. Of these, 1242 are students of higher education while the remaining 346 attend secondary school. Taking into account the specificities of each of these educational groups, two versions of the questionnaire were built, specifically designed for the two different contexts addressed. In these first results, it can be seen a very poor level of cognitive skills to select, search, elaborate and filter information as well as a lack of an educational and librarian/informational policy that better fits and encourages an appropriate performance by students. Hence the importance and usefulness of eLit.pt model that aims to show and to operationalize the articulation of cognitive skills in information behavior and to articulate the role of libraries (school, public and university) teachers, education system and "informal groups".